Transcriptome profiling reveals the complexity of pirfenidone effects in idiopathic pulmonary fibrosis. Issue 5 (22nd November 2018) - Kwapiszewska, Grazyna; Gungl, Anna; Wilhelm, Jochen; Marsh, Leigh M.; Thekkekara Puthenparampil, Helene; Sinn, Katharina; Didiasova, Miroslava; Klepetko, Walter; Kosanovic, Djuro; Schermuly, Ralph T.; Wujak, Lukasz; Weiss, Benjamin; et al.
Despite the beneficial effects of pirfenidone in treating idiopathic pulmonary fibrosis (IPF), it remains unclear if lung fibroblasts (FB) are the main therapeutic target. To resolve this question, we employed a comparative transcriptomic approach and analysed lung homogenates (LH) and FB derived from IPF patients treated with or without pirfenidone. In FB, pirfenidone therapy predominantly affected growth and cell division pathways, indicating a major cellular metabolic shift. In LH samples, pirfenidone treatment was mostly associated with inflammation-related processes. In FB and LH, regulated genes were over-represented in the Gene Ontology node "extracellular matrix". We identified lower expression of cell migration-inducing and hyaluronan-binding protein (CEMIP) in both LH and FB from pirfenidone-treated IPF patients. Plasma levels of CEMIP were elevated in IPF patients compared to healthy controls and decreased after 7 months of pirfenidone treatment. CEMIP expression in FB was downregulated in a glioma-associated oncogene homologue-dependent manner and CEMIP silencing in IPF FB reduced collagen production and attenuated cell proliferation and migration. Cumulatively, our approach indicates that pirfenidone exerts beneficial effects via its action on multiple pathways in both FB and other pulmonary cells, through its ability to control extracellular matrix architecture and inflammatory reactions. Pirfenidone's mode of action in human lungs involves a complex interactome comprising genes related to inflammation and extracellular matrix architecture http://ow.ly/26NN30lpGON